Integration of Sustainability Indicators in Regional Road Policy: East Kolaka, Indonesia - Puspita, Rika; Gani, Abdul Juli Andi; Shobaruddin, Muhammad (Publica: Jurnal Pemikiran Administrasi Negara, 2025)
The suboptimal integration of sustainability indicators in regional road policies in East Kolaka Regency, Indonesia, has resulted in infrastructure development that does not pay attention to environmental, social and economic aspects in a balanced manner. This study aims to analyze the integration of sustainability indicators and identify implementation barriers in regional road infrastructure policies in East Kolaka Regency. Employing a qualitative approach and thematic analysis, data were collected through in-depth interviews, field observations, and document reviews involving key actors from government agencies, civil society, and the private sector. The findings reveal that sustainability integration has been pursued through the use of environmentally friendly technologies, improved economic connectivity through agropolitan strategies, and community participation in planning processes. However, implementation remains challenged by complex geographic conditions, limited human and financial resources, political interventions, and administrative constraints. These findings highlight the importance of localized sustainability indicators and the need for improved governance and inter-agency coordination to achieve inclusive and sustainable road development.